Psychometric Properties of the German School Refusal Assessment Scale–Revised. (September 2018) - Walter, Daniel; von Bialy, Johanna; von Wirth, Elena; Doepfner, Manfred
The School Refusal Assessment Scale–Revised (SRAS-R) is a widely used measure of the functional conditions leading to school absenteeism. In the present study, we developed a German version of the SRAS-R and investigated its psychometric properties in a clinical sample ( N = 62) of referred school absentees aged 11 to 17 years. Results of an exploratory factor analysis revealed a four-factor solution for the self-rated version and a three-factor solution for the parent-rated version. All four subscales of the final 22-item German SRAS-R were internally consistent. Convergent and discriminant validity were shown by significant correlations with other scales assessing internalizing and externalizing symptoms. Overall, the German SRAS-R is a valuable instrument for assessing school absenting behavior. The results should be interpreted conservatively due to the limited sample size.